Embedding Soft Skills in Health Professions Education: A Knowledge, Attitudes and Practice (KAP) Inquiry on Pedagogical Approaches and Barriers - Perea, Kenneth (International Journal of Education, Research, and Innovation Perspectives, 2026)
Soft skills are essential competencies in health professions education, yet their integration remains inconsistent across programs. This convergent parallel mixed-methods study examined the knowledge, attitudes, and practices of allied health educators regarding soft-skills integration, including the pedagogical approaches used and barriers encountered. Thirty-nine educators from Nursing, Pharmacy, Medical Technology, Physical Therapy, and Radiologic Technology programs at the University of Perpetual Help System DALTA–Calamba participated in the quantitative phase, while 10 selected participants joined semi-structured interviews. Data were gathered using a validated researcher-made KAP questionnaire and analyzed through descriptive statistics, t-tests, ANOVA, Tukey HSD, and thematic analysis. Findings revealed that educators had adequate knowledge and positive attitudes toward soft-skills integration, but implementation was only sometimes practiced. Traditional instructional approaches were most frequently used, followed by experiential, collaborative, reflective, and technology-enhanced methods. Qualitative findings emphasized structured assessment, reflective learning, educator role-modeling, simulation-based instruction, feedback culture, and technology-mediated learning, while barriers included limited time, curricular overload, insufficient faculty training, and competing instructional priorities. The study concludes that while allied health educators recognize the importance of soft skills, stronger institutional support, faculty development, assessment tools, and curriculum enhancement are needed to ensure consistent and meaningful integration.